Grinding-induced solvent-free synthesis of mesoporous zirconia-supported tungsten oxide composite and its superior oxidative desulfurization performance. (1st May 2022) - Zhou, Lina; Du, Yue; Jin, Yongxu; Chen, Wenxue; Pan, Qiyun; Kai, Wang; Liu, Yisi; Yang, Lun; Liu, Zhenhui
Graphical abstract: Highlights: An effective solvent-free self-assembly strategy has been investigated to the fast and effective synthesis of mesoporous zirconia-supported tungsten oxide composite; As fabricated mesoporous zirconia-supported tungsten oxide composite possesses remarkable porous properties; Mesoporous zirconia-supported tungsten oxide catalyst demonstrates excellent catalytic efficiency and stability in oxidative desulfurization process. Abstract: Mesoporous ZrO2 with remarkable pore properties and high crystallinity has demonstrated excellent performance in heterogeneous catalyst fields. Current synthesis of mesoporous ZrO2 is still restricted to the solvent induced self-assembly strategy. Here, a serial of mesoporous zirconia-supported tungsten oxide composites have been synthesized by a polymer-oriented solvent-free self-assembly method. Compared with quaternary ammonium salts cationic surfactant and Pluronic block copolymer, cheap and widely available polyethyleneimine (PEI) polymer has been proved to be a more effective porogen in the solvent-free self-assembly system, which can generate uniform-sized ZrO2 nanoparticles and maintain their porous structure after high temperature calcination. PEI-oriented mesoporous zirconia-supported tungsten oxide composite provides connected channels for reactant and facilitates the homogeneous distribution of tungsten oxide species on mesoporous ZrO2 matrix, which demonstrates excellent catalytic efficiency and stability in oxidative desulfurization (ODS) process. 500 ppm of dibenzothiophene (DBT) can be totally removed within 2 h at 40 °C.